Amwal Zakat Management: A Case Study in Yogyakarta - Waharjani, Waharjani; Jailani, Mohammad (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2022)
Abstract. Zakāh collection in Nitikan village of Yogyakarta has experienced an increase since 2017, which previously had been stagnant. This paper aims to investigate the current development of the zakāh collection in that area, as it represents Muhammadiyah's efforts in the religious philanthropic movement. T his is a qualitative study, with the data obtained from participatory observation and in-depth interviews with zakāh stakeholders. This study finds that the improvement of the zakāh collection has contributed to several factors. These include the role of ulama and Bapelurzam of Muhammadiyah, leading to the increasing trust of the people. This is strengthened by the changing paradigm of the muzakki regarding zakāh al-māl from merely gold and silver into any properties equal to niṣāb and has reached the haul; and the strong determination of mustaḥiq to transform themselves into muzakki.Abstrak. Penghimpunan zakat di desa Nitikan Yogyakarta mengalami peningkatan sejak tahun 2017 yang sebelumnya stagnan. Studi ini bertujuan untuk mengetahui perkembangan penghimpunan zakat di daerah tersebut, sebagai representasi dari upaya Muhammadiyah dalam gerakan filantropi Islam. Penelitian ini merupakan penelitian kualitatif, dengan data yang diperoleh dari observasi partisipatif dan wawancara mendalam dengan pemangku kepentingan zakat. Studi ini menemukan ada beberapa faktor yang berkontribusi dalam peningkatan zakat di Nitikan. Diantaranya adalah peran ulama dan Bapelurzam Muhammadiyah yang berdampak pada meningkatnya kepercayaan masyarakat. Hal ini diperkuat dengan perubahan paradigma muzakki tentang zakat mal dari semula terbatas pada emas dan perak menjadi harta apapun yang setara nisab zakat mal dan telah mencapai haul; serta tekad kuat mustahiq untuk bertransformasi menjadi muzakki.